2009
DOI: 10.1242/jcs.054916
|View full text |Cite
|
Sign up to set email alerts
|

Defining specificity of transcription factor regulatory activities

Abstract: the genome, and of chromatin structure and gene expression, have allowed a better understanding of the general rules that underlie the differential activities of a given TF. It has emerged that chromatin structure dictates the differential binding of a given TF to cell-type-specific cis-regulatory elements. The subsequent regulation of TF activity then ensures the functional activation of only the precise subset of all regulatory sites bound by the TF that are required to mediate appropriate gene expression. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 120 publications
1
17
0
Order By: Relevance
“…Many transcription factors are shown to both activate and repress gene expression depending on sequence, chromatin structure and modulators (19,20). It is also well documented that the modulators affect a specific subset of the targets of a transcription factor (21,22), and can reverse their effect based on the target gene (23,24). Several genome-wide studies show that such complicated cases in fact might be very common (25–28).…”
Section: Resultsmentioning
confidence: 99%
“…Many transcription factors are shown to both activate and repress gene expression depending on sequence, chromatin structure and modulators (19,20). It is also well documented that the modulators affect a specific subset of the targets of a transcription factor (21,22), and can reverse their effect based on the target gene (23,24). Several genome-wide studies show that such complicated cases in fact might be very common (25–28).…”
Section: Resultsmentioning
confidence: 99%
“…A general problem that emerges from genome-wide studies is the evidence that the number of interactions made between the BSs of a transcription factor and genes promoters is not systematically reflected at the transcriptional level (74). The use of TFOs allowed us to provide further indications on how binding sites for a transcription factor are mobilized in space and time in order to regulate the transcription of its target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the availability of co-factors or cellular stimulators, such as estrogen, in different cellular contexts in different tumor developing stages may also affect the binding sites for the same transcription factor. 42 Therefore, our study found three out of 18 putative genes could be remarkably upregulated by enforced expression of FOXM1. Further biochemical and functional analyses revealed that DLX1 is a direct target of FOXM1 in mediating cell migration/invasion of high-grade serous ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 65%
“…41 This difference in the FOXM1-binding sites may be due to a cell type- and context-specific sequences. 42 For example, a recent study used MCF7 breast cancer cells to investigate FOXM1-binding, while we used ovarian cancer cells in this study. Moreover, the availability of co-factors or cellular stimulators, such as estrogen, in different cellular contexts in different tumor developing stages may also affect the binding sites for the same transcription factor.…”
Section: Discussionmentioning
confidence: 99%